Dukungan Sosial pada Pasien Post Total Knee Replacement : Literature Riview - Widiastuti, Agung; Arofiati, Fitri (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Ostheoatritis disease become triggers to do Total Knee Replacement (TKR). Patients TKR will experience pain, physical limitations and muscle stiffness that causes a quite long recovery. The effects  quite  long recovery can influence quality of life. It can be measured using WOMAC scale (The Western Ontario and McMaster Universities Osteoarthritis Index). Objective: Knowing the influence of social support on post-operation TKR patient recovery. Method: Searching relevant for data base literature sources using Ebsco, Pubmed, Sciencedirect, and Google Scholar search engine using Keywords: Social Support, Level Independence, Quality Of Life, Total Knee Replacement, from the searching Appropriate results with the inclusion and exclusion criteria, that can be eight articles include literature review where the article is taken to pressure quality of  life which uses the WOMAC scale. Result : There are seven of Eight articles state social support can influence the quality of life to TKR  recovery and one study haven’t Influence, because age, complication, and don’t live with family. Conclusion: Social support proven to influence health status and quality of life in TKR patients recovery.